Kaana (كَانَ) Dalam Surah Al-Isra` (Suatu Analisis Nahwu Dan Terjemahnya) - Mukammiluddin Mukammiluddin (Jurnal Adabiyah: Humanities and Islamic Studies, 2013)
There are amount of linguistic terms utilized in al-Quran. One of the is kana and its derivation. This world has various fuction and meaning based on where it is placed or positioned. Kana can be used as the completion of ayat that actually has no meaning, but it determines the pattern of ayat, and sometime it has substantial meaning that determines the position of time where ayat was revealed down or used in textual or contextual meaning.